2015
DOI: 10.1007/s12015-015-9602-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Myocardial Infarction 2001–2013 Revisited

Abstract: Stem cell therapy for ischemic heart disease was an emerging concept in the early 2000s. First hopes were largely overshadowed by rather inconsistent results in human trials conducted in the middle of the decade. We aimed at investigating how the field of stem cell research expanded worldwide over the years using scientometric methods. We performed a PubMed inquiry and screened a total of 2609 publications dealing with stem cell therapy for myocardial infarction in the years 2001-2013. Density equalizing maps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Over the past few decades, stem cell-based therapy has emerged as a promising therapeutic approach for ischemic cardiac repair and regeneration. 19 Endothelial progenitor cells derived from bone marrow or peripheral blood have been tested in clinical studies. However, myocardial infarction, the leading cause of death in U.S. patients, triggers an intense immune response and greatly decreases the therapeutic effects of EPC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, stem cell-based therapy has emerged as a promising therapeutic approach for ischemic cardiac repair and regeneration. 19 Endothelial progenitor cells derived from bone marrow or peripheral blood have been tested in clinical studies. However, myocardial infarction, the leading cause of death in U.S. patients, triggers an intense immune response and greatly decreases the therapeutic effects of EPC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, Gnecchi et al reported that conditioned medium of mesenchymal stem cells alone markedly reduced cell death in rat cardiomyoctes exposed to hypoxia . Therefore, in the following years focus has shifted from stem‐cell therapy to paracrine mechanisms via cytokines, chemokines, and growth factors . In several studies cell‐free approaches by administration of supernatants of cells alone, could be shown to have beneficial effects on cytoprotection and inhibition on tissue remodeling after AMI .…”
Section: Introductionmentioning
confidence: 99%
“…The initial hope that stem cell therapy has a benefit was disappointed by several large clinical trials. [2][3][4][5]. Consequently, the so-called "paracrine paradigm" was formulated stating not the stem cells themselves but their secretomes are responsible for some of the promising results in clinical trials investigating "stem cell" therapy [10,11].…”
Section: Discussionmentioning
confidence: 99%